Business model innovation: A review and research agenda - Boumediene Ramdani; Ahmed Binsaif; Elias Boukrami (New England Journal of Entrepreneurship (NEJE), 2019)
Purpose The aim of this paper is to review and synthesise the recent advancements in the business model literature and explore how firms approach business model innovation. Design/methodology/approach A systematic review of business model innovation literature was carried out by analysing 219 papers published between 2010 and 2016. Findings Evidence reviewed suggests that rather than taking either an evolutionary process of continuous revision, adaptation and fine-tuning of the existing business model or a revolutionary process of replacing the existing business model, firms can explore alternative business models through experimentation, open and disruptive innovations. It was also found that changing business models encompasses modifying a single element, altering multiple elements simultaneously and/or changing the interactions between elements in four areas of innovation: value proposition, operational value, human capital and financial value. Research limitations/implications Although this review highlights the different avenues to business model innovation, the mechanisms by which firms can change their business models and the external factors associated with such change remain unexplored. Practical implications The business model innovation framework can be used by practitioners as a "navigation map" to determine where and how to change their existing business models. Originality/value Because conflicting approaches exist in the literature on how firms change their business models, the review synthesises these approaches and provides a clear guidance as to the ways through which business model innovation can be undertaken.
Keywords: 650; Innovation; Business model; Value proposition; Value creation; Value capture